Immunopurification of Mitochondria from Arabidopsis. Issue 2 (8th February 2021) - Luo, Lilan; He, Yajun; Li, Jiayang; Yu, Hong
Abstract: Isolation of mitochondria from plant tissues, especially green leaves, is particularly difficult because of chloroplast contamination. Compared to other techniques for purifying plant mitochondria, the immunopurification method has a number of advantages: it rapidly purifies the mitochondria within several minutes, avoids loss of mitochondrial metabolites, eliminates most other organelles (especially the chloroplasts), keeps the isolated mitochondria intact, requires little starting material, and has the potential to purify tissue‐specific mitochondria. Here, we describe a rapid immunopurification protocol for mitochondrial isolation that employs a protein specifically targeted to the outer mitochondrial membrane that acts as an immunopurification handle. © 2021 Wiley Periodicals LLC.